Investigating the associations of macular edema in retinitis pigmentosa - Juan D. Arias; Fritz Gerald P. Kalaw; Varsha Alex; Shaden H. Yassin; Henry Ferreyra; Evan Walker; Naomi E. Wagner; Shyamanga Borooah (Scientific Reports, 2023)
Abstract Macular edema (ME), the accumulation of intraretinal fluid in the macula, is a common sight affecting sequelae of retinitis pigmentosa (RP). However, it is unclear why some patients develop ME, and others do not. This study aims to identify associations between clinical-genetic factors in RP with ME. Patients with clinically confirmed RP cases were identified from the inherited retinal disease database at a large tertiary referral academic center. Demographic and genetic testing findings were noted. Additionally, optical coherence tomography volume scans were graded using a validated grading system. One hundred and six patients (73.1%) were found to have ME in at least one eye (OD = 88, mean = 37.9%, OS = 98, mean = 31.7%). Structurally, the presence of epiretinal membrane (ERM) (p < 0.007) and vitreo-macular traction (VMT) (p < 0.003) were significantly associated with ME. Additionally, X-linked (p < 0.032) and autosomal dominant inheritance (p < 0.039) demonstrated a significant association with ME, with RP1 (p < 0.045) and EYS (p < 0.017) pathogenic variants also significantly associated with ME. This study, in a large cohort of RP patients, confirms previous retinal structural associations for ME in RP and identifies potential new genetic associations.